(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
The aim of this paper is to present the opinions, experiences and needs of a sample of scientists in the field of the humanities – namely historians and philologists – and their use of newspaper collections in memory institutions during scientific research. A part of the results gathered in the research, which was conducted within the Newspapers as a source of scientific information in social sciences and humanities project, and is presented here. This project examined the extent and practices in the use of newspapers as a resource of information for scientific research in the social sciences and humanities field in Croatia. The quantitative and qualitative data about the methods and level of use of newspaper material as a resource in scientific research were gathered. The results of this project implied that the newspapers are recognised and used as an admissible resource in scientific work, especially in the fields of history and philology. The fact that scientists have specific information needs and search patterns should be considered in creating innovative and effective digital newspaper collections.